An Analysis of Translation Techniques Found in "Wish" Movie - Desak Made Indah Fitriawati; Ni Made Verayanti Utami (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The study entitled An Analysis of Translation Techniques Found In “Wish” Movie. The study aims to observe the types of translation techniques that are used and which types are dominant in this movie. The data were obtained by descriptive qualitative method and the data was analyzed based on the theory by Molina & Albir (2002). The researcher found adaptation (8,5%), amplification (0,5%), borrowing (2,6%), calque (1,3%), Compensation (0,1%), Established equivalent (0,7%), Generalization (0,8%), Linguistic compression (2,4%), Literal translation (74,4%), Modulation (1,7%), particularization (0,1%), reduction (6,1%), substitution (0,5%), transposition (0,1%), and variation (0,4%). Therefore, the dominant translation technique used in the movie "Wish" is literal translation. Literal translation is more likely to be used in subtitling because it keeps the original dialog faithful. Literal translation allows the audience to understand what was said in the source language.